2014
DOI: 10.1016/j.vaccine.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of rotavirus strains identified in adolescents and adults with acute gastroenteritis highlights circulation of non-typeable strains: 2008–2012

Abstract: The study underscores the significant temporal variations in RV strains, identifies circulation of intergenogroup reassortants among adolescent and adult patients with acute gastroenteritis and emphasizes the need for continued surveillance and whole genome analysis of emerging rotavirus strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Previous studies have described RVA in adults pre‐ and post massive introduction of RVA vaccination [Nakajima et al, ; Morillo et al, ; Gunn et al, ; Anandan et al, ; Kirkwood and Roczo‐Farkas, ; Kittigul et al, ; Luchs et al, ; Tatte et al, ; Anderson et al, ; Pacilli et al, ]. In our data, G12P[8] was observed in high prevalence in adults, in accordance with previous reports reinforcing the idea that adults may have more RVA infections than previously reported.…”
Section: Resultssupporting
confidence: 92%
“…Previous studies have described RVA in adults pre‐ and post massive introduction of RVA vaccination [Nakajima et al, ; Morillo et al, ; Gunn et al, ; Anandan et al, ; Kirkwood and Roczo‐Farkas, ; Kittigul et al, ; Luchs et al, ; Tatte et al, ; Anderson et al, ; Pacilli et al, ]. In our data, G12P[8] was observed in high prevalence in adults, in accordance with previous reports reinforcing the idea that adults may have more RVA infections than previously reported.…”
Section: Resultssupporting
confidence: 92%
“…The significant proportion of partially typed samples, which we found in the control group, may be explained by the fact that controls may excrete less virus than children with more severe diarrhoea, as observed by other groups [51]. In addition to this, few available studies that investigated rotavirus on LSD cases have reported a high proportion of non-typeable strains [52,53]. A study in India reported 80% and another in China 24% [52,53].…”
Section: Discussionmentioning
confidence: 58%
“…In Latin America, the prevalence of G9P[4], which had been found in 0.4% of RVA cases, remarkably increased in 2009–2010 [Quaye et al, ]. A recent study reported that a G9P[4] strain having I2‐type VP6 and E6‐type NSP4, which is identical VP7‐VP4‐VP6‐NSP4 set with G9P[4] strain in Latin America, was detected in India during 2010–2011, suggesting that a certain G9P[4] strain may be circulating globally [Quaye et al, ; Tatte et al, ]. The phylogenetic analysis of the G9P[4] strain in Japan, which includes its unique genome constellation possessing genotype 2 internal protein genes except for the T1‐type NSP3 gene, revealed that this strain is distinct from other reported G9P[4] strains but closely related to co‐circulating Japanese G9P[8] strain in VP7 and NSP3 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Putative binding domains (BD) in NSP3 with RNA, RoXaN, and eIF4G were indicated as RNA-BD, RoXaN-BD, and eIF4G-BD, respectively [Arnold et al, 2012]. strain in Latin America, was detected in India during 2010-2011, suggesting that a certain G9P[4] strain may be circulating globally [Quaye et al, 2013;Tatte et al, 2014]. The phylogenetic analysis of the G9P[4] strain in Japan, which includes its unique genome constellation possessing genotype 2 internal protein genes except for the T1-type NSP3 gene, revealed that this strain is distinct from other reported G9P[4] strains but closely related to co-circulating Japanese G9P[8] strain in VP7 and NSP3 genes.…”
Section: Discussionmentioning
confidence: 99%